THE INFLUENCE OF SHORT MATERNAL HEIGHT ON STUNTING CHILDREN - Kamila Fadma Putri Sumarsono; Irwanto Irwanto (UNIVERSITAS AIRLANGGA, 2022)
Stunting is a condition of chronic malnutrition caused by inadequate nutritional intake over a long period. This condition is represented by a child's height based on age less than minus 2 standard deviations (<-2SD) from the WHO Child Growth Standard. Stunting has long-term effects on children's health and intelligence. This study aims to analyze the effect of short maternal height on the incidence of stunting in the working area of the Raci Health Center. An observational analytic study with a case control approach was conducted in March-May 2021. The research sample consist of 130 mothers and children according to the inclusion and exclusion criteria and using purposive sampling technique. The independent variable in this study was maternal height and the dependent variable was stunting. Chi square statistical test was used to determine the level of significance in the data. Bivariate result showed that maternal height affected the incidence of stunting with ρ =0.003 and OR=3.222. Mother's height is a risk factor for stunting in children in the working area of Raci Health Center.